Metaplastic carcinoma of the breast: A report of two cases - Ganesan, Keerthini; Sundaram, Sandhya; Joseph, Leena Dennis (Annals of Pathology and Laboratory Medicine, 2019)
Metaplastic carcinoma of the breast is a rare tumor which accounts for less than 1% of all the primary breast malignancies. It commonly occurs in women more than 50 years of age and are usually triple negative tumors with basal like subtype. Metaplastic carcinomas of breast have a very aggressive behaviour resulting in worse prognosis and a dismal disease free survival. However most metaplastic carcinomas express EGFR, therefore early and correct diagnosis benefits the patient to receive anti-EGFR drugs like cetuximab and geftinib. We are reporting two cases of metaplastic carcinomas, one with spindle cell differentiation and the other with squamous differentiation.